Evaluating Strategic Agility Implementation In Increasing The Effectiveness Of Crisis Management In The Coast Company Of Yarn In Jableh - اسبر, لمى (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims at highlighting the concept Strategic Agility, and the necessity of being agile in order to increase the effectiveness of crisis management, that crisis occurred naturally in Business world where confusing and uncertainty increases. The research was conducted in The Coast Company of Yarn in Jableh on a sample of managers in all administrative levels, 29 questionnaires were distributed to obtain answers on studied subject, descriptive analysis and statistical inference were used to reach the results.by using SPSS 20. The study finds: there is a weakness in implementing strategic agility to increase effectiveness of crisis management in the studied company, and managers are practicing in traditional ways for planning, controlling and making decisions. The research recommends to: Concentrate on sensing activities especially for companies with limited resources. Put several scenarios to manage contingency circumstances. Simplify the organizational structure and increase delegation. Create a flexible workforce.